Case report: A rare multidrug-resistant Escherichia coli causes fatal neonatal meningoencephalitis - Zhou, Qingyun; Zhan, Zhifei; Huang, Furong; Zhao, Menghua; Huang, Daosheng; Xu, Jun; Huang, Li; Xie, Liangyi; Zhang, Aimin (Frontiers in Public Health, 2023)
Neonatal meningitis is rare but devastating disease. Multidrug-resistant (MDR, multi-drug resistant) bacteria are a major global health risk. We report an Escherichia coli meningitis isolate with multiple resistance patterns and unusual serotype (O75) that caused sudden neonatal death. The isolate was resistant to antibiotics other than cefoperazone/sulbactam and imipenem, challenging the combination of antibiotics commonly used in the empirical treatment of neonatal sepsis. Despite aggressive symptomatic and supportive treatment of the infant based on laboratory tests and clinical practice, the infant eventually died. This is the first case of meningoencephalitis due to serotype O75 reported in China. The presence of highly pathogenic multidrug-resistant microorganisms isolated in neonates underscores the need to implement rapid resistance diagnostic methods and should prompt consideration of alternatives to empiric treatment of neonatal bacterial meningitis.